Neonatal Morbidities among Moderately Preterm Infants with and without Exposure to Antenatal Corticosteroids - Chawla, Sanjay (Am J Perinatol, 2018)
OBJECTIVE: We aimed to compare the rates of “surfactant treated respiratory disease” and other neonatal morbidities among moderately preterm (MPT) infants exposed to no, partial, or a complete course of antenatal corticosteroids (ANS). STUDY DESIGN: This observational cohort study evaluated MPT infants (29(0/7)–33(6/7) weeks’ gestational age), born between January 2012 and November 2013 and enrolled in the “MPT Registry” of the National Institute of Child Health and Human Development Neonatal Research Network. RESULTS: Data were available for 5,886 infants, including 676 with no exposure, 1225 with partial, and 3,985 with a complete course of ANS. Among no, partial, and complete ANS groups, respectively, there were significant differences in rates of delivery room resuscitation (4.1, 1.4, and 1.2%), surfactant-treated respiratory disease (26.5, 26.3, and 20%), and severe intracranial hemorrhage (3, 2, and 0.8%). Complete ANS course was associated with lower surfactant-treated respiratory disease, compared with partial ANS (odds ratio [OR] 0.62; 95% confidence interval [CI] 0.52–0.74), and no ANS groups (OR 0.52; 95% CI 0.41–0.66) on adjusted analysis. CONCLUSION: In MPT infants, ANS exposure is associated with lower delivery room resuscitation, surfactant-treated respiratory disease, and severe intracranial hemorrhage; with the lowest frequency of morbidities associated with a complete course.